Investigating the Role of Interactive Activities in Enhancing Pre-Intermediate English Grammar Learning: A Qualitative Inquiry at Universitas Klabat - Nurhayati Nurhayati; Stenlly Sedubun (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
This research aims to analyze Investigating the Role of Interactive Activities in Enhancing Pre-Intermediate English Grammar Learning: A Qualitative Inquiry at Klabat University. The type of research is descriptive qualitative. Data collection techniques using observation, interviews and documentation. Data analysis techniques using data reduction, data display and conclusions. research results The qualitative inquiry conducted at Klabat University delves into the significant role of interactive activities in bolstering pre-intermediate English grammar learning. Through meticulous observation and analysis, it becomes evident that interactive activities not only engage learners actively in the learning process but also facilitate a deeper understanding and retention of grammatical concepts. By fostering collaborative learning environments and promoting meaningful interactions, these activities cater to diverse learning styles and encourage students to actively participate in their own language acquisition journey. Thus, integrating interactive activities into English grammar instruction proves instrumental in enhancing the overall learning experience and proficiency levels of pre-intermediate learners at Klabat University.